Efektivitas Pembelajaran PAK Berdimensi Gotong Royong Dengan Metode PBL Fase B SD Kebon Dalem Semarang (International Forum of Researchers and Lecturers, 2023)
Student learning outcomes are very low due to the lack of use of interesting methods in learning activities. The research aims to: 1) Find out whether the PBL method can achieve the learning achievement targets for class IV students, 2) find out the increase in learning achievement for class IV students before and after the PBL method is implemented, 3) Find out the influence of the mutual cooperation aspect in learning using the PBL method on learning achievement fourth grade students. Experimental quantitative assessment using one class. There were 20 samples in the experimental class. The results of the study explain that: 1) the average posttest learning achievement increased through the use of the PBL method thereby increasing the class average by 87, 2) there was an increase in learning achievement from pretest to posttest in the experimental class by 68%, including quite effective use of the PBL method, and 3) there is a positive influence of the mutual cooperation aspect on learning achievement of 86.1%. Conclusion: The mutual cooperation aspect using the PBL method influences student learning outcomes and this research can also be used as a reference to develop further discussion.